Children and Young People's Participation in Disaster Risk Reduction Agency and Resilience - Mort, Maggie; Rodríguez-Giralt, Israel; Delicado, Ana (Policy Press, 2020)
"Available Open Access under CC-BY-NC licence. Disasters are complex environmental, social and cultural events and processes yet disaster management approaches tend to simplify responses and homogenise affected populations. Participatory research with more than 550 children across Europe, detailed in this book argues for a radical transformation in children's roles in disasters. It shows how more child-centred working in civil protection and emergency planning, that recognises children's capacities in building resilience, benefits at-risk communities as a whole. "